Stress-induced expression is enriched for evolutionarily young genes in diverse budding yeasts - Tyler W. Doughty (Nature Portfolio, 2020)
Fermentation parameters of industrial processes are often not the ideal growth conditions for industrial microbes. Here, the authors reveal that young genes are more responsive to environmental stress than ancient genes using a new gene age assignment method and provide targeted genes for metabolic engineering.